2015
DOI: 10.1016/j.compositesa.2015.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Can thermally degraded glass fibre be regenerated for closed-loop recycling of thermosetting composites?

Abstract: Commercially manufactured E-glass fibres were heat-conditioned to mimic the effects of thermal recycling of glass fibre thermosetting composites. Degradation in the strength and surface functionality of heat-treated fibres was identified as a key barrier to reusing the fibres as valuable reinforcement in composite applications. A chemical approach has been developed to address these issues and this included two individual chemical treatments, namely chemical etching and post-silanisation. The effectiveness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 14 publications
2
67
1
6
Order By: Relevance
“…Consequently, the loss in reinforcement performance of the RGF compared to pristine GF is actually proportionally much greater than the measured loss in composite performance. This has been confirmed in recent work by Thomason et al [17,119] and Yang et al [120], where heat-conditioned fibres were used to produce RGF-PP composites and RGF-epoxy composites. In both cases, reference values for the polymer matrix were produced, and in both cases, the tensile strength of the RGF composites was a little better than the unreinforced polymer matrix.…”
Section: Glass Fibre Recycling and Reuse As Reinforcementssupporting
confidence: 65%
See 2 more Smart Citations
“…Consequently, the loss in reinforcement performance of the RGF compared to pristine GF is actually proportionally much greater than the measured loss in composite performance. This has been confirmed in recent work by Thomason et al [17,119] and Yang et al [120], where heat-conditioned fibres were used to produce RGF-PP composites and RGF-epoxy composites. In both cases, reference values for the polymer matrix were produced, and in both cases, the tensile strength of the RGF composites was a little better than the unreinforced polymer matrix.…”
Section: Glass Fibre Recycling and Reuse As Reinforcementssupporting
confidence: 65%
“…A very recent paper by Yang et al further explored the potential of HF treatment in glass fibre recovery [120]. They reported on a systematic study of the effects of heat treatment, HF treatment and silane treatment on the strength of boron-free E-glass fibres and RGF-epoxy composites produced by vacuum infusion moulding.…”
Section: Glass Fibre Strength Regeneration and Reusementioning
confidence: 99%
See 1 more Smart Citation
“…We have recently developed a simple chemical approach to address this key issue and have successfully proved that these damaged filaments can be reused as reinforcements again if their strength is restored [11]. It was found that the strength of glass fibres heat-conditioned at 450-600°C can almost triple after a few minutes of immersion in dilute hydrofluoric acid (HF) [12]. HF is proven to be an effective chemical etchant and is thought to strengthen glass by removing surface flaws [13].…”
Section: Introductionmentioning
confidence: 99%
“…As a preliminary conclusion, they summarize that heat-treated fibers with HF treatment followed by silanisation resulted in composites with high levels of composite performance recovery. The authors also review their own work [6,7] on 'non-HF based (e.g., short treatment in hot NaOH solution and further application of a silane sizing) glass fiber strength regeneration treatment towards a cost-effective closed-loop glass fiber recycling technology'. It should be mentioned that this review highlights the available knowledge on the thermally induced strength loss in recycling of glass fibers, discusses some of the related phenomena, and presents the status of research, besides many open questions connected with surface flaws, glass fiber durability, repair of fiber surfaces and interphase built-up in composites.…”
mentioning
confidence: 99%